ANALYSIS OF FILARIASIS CASES IN PAYA LAOT VILLAGE, SETIA BAKTI SUBDISTRICT - Lensoni; Mushaithir (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Filariasis is a chronic infectious disease caused by filarial worms and transmitted by Mansonia, Anopheles, Culex, Armigeres mosquitoes. One of the Filariasis endemic areas is in Paya Laot Village, Setia Bakti Regency, therefore all residents in Paya Laot Village are required to take Filariasis prevention drugs. The purpose of this study was to analyze the implementation of the elephantiasis control program in Setia Bakti district. This research is descriptive research, data collection is done by in-depth interviews. The results showed that the implementation of the elephantiasis control program was optimal because all the main tasks in the program had been carried out and achieved the set targets, but for vector control there was no special supervision and there were still many people who were afraid to take elephantiasis prevention drugs because they could cause side effects. The elephantiasis control program is carried out from 2019 to 2023, the coverage of drug administration achieved in Paya Laot Village, Setia Bakti Regency is 89% of the target number who took the drug and 83% who took the drug from the population in 2019, 90% of the target number who took the drug and 82% who took the drug from the population in 2023. Based on the results of the study, it is hoped that the Health Office of the loyal bakti Regency will supervise vector control and socialization to people who are still afraid to take elephantiasis prevention drugs.